2007
DOI: 10.1038/nrn2196
|View full text |Cite
|
Sign up to set email alerts
|

Translational principles of deep brain stimulation

Abstract: Deep brain stimulation (DBS) has shown remarkable therapeutic benefits for patients with otherwise treatment-resistant movement and affective disorders. This technique is not only clinically useful, but it can also provide new insights into fundamental brain functions through direct manipulation of both local and distributed brain networks in many different species. In particular, DBS can be used in conjunction with non-invasive neuroimaging methods such as magnetoencephalography to map the fundamental mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
557
1
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 744 publications
(571 citation statements)
references
References 137 publications
3
557
1
10
Order By: Relevance
“…The early finding that DBS of the STN or GPi results in clinical benefits that are strikingly similar to those of lesioning at these sites for tremor and PD, respectively, suggested initially that DBS may act by inhibiting neurons in the area of stimulation [269][270][271]. This view was supported by the demonstration that some neurons in the vicinity of the stimulation site in STN and GPi in experimental animals and in patients with PD are, indeed, inhibited [272][273][274][275], perhaps by depolarization block or the release of GABA from terminals of afferents to the stimulated area [276][277][278][279][280].…”
Section: Dbs Mechanism Of Actionmentioning
confidence: 83%
See 2 more Smart Citations
“…The early finding that DBS of the STN or GPi results in clinical benefits that are strikingly similar to those of lesioning at these sites for tremor and PD, respectively, suggested initially that DBS may act by inhibiting neurons in the area of stimulation [269][270][271]. This view was supported by the demonstration that some neurons in the vicinity of the stimulation site in STN and GPi in experimental animals and in patients with PD are, indeed, inhibited [272][273][274][275], perhaps by depolarization block or the release of GABA from terminals of afferents to the stimulated area [276][277][278][279][280].…”
Section: Dbs Mechanism Of Actionmentioning
confidence: 83%
“…Later electrophysiologic recording studies in primates and patients demonstrated that DBS has, in fact, multiple actions that may differ with the distance from the stimulation site and the spatial orientation of electrodes and neural elements studied [276,277]. Axons are known to be more sensitive to stimulation than cell bodies [276,277,[281][282][283], so that highfrequency DBS may alter the activity of axons emerging from a given area (this was specifically shown for STN and GPe DBS [283,284]), thus leading to a functional blockade of transmission of information, whether pathological or normal, through the stimulated area, but without silencing of the tissue.…”
Section: Dbs Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…7). Originally discovered in rats and conceived as activating pleasure centers in the brain (Olds 1956), recent reappraisal have been prompted by observations that such electrodes may cause increased 'wanting' without 'liking' for rewards, similar to dopamine (Berridge 2003b;Green et al 2008;Kringelbach 2008;Kringelbach et al 2007b;Smith et al 2008). Brain stimulation electrodes are vigorously selfstimulated by rats in structures such as lateral hypothalamus, septum, accumbens, or the medial forebrain bundle (Olds and Milner 1954;Shizgal et al 2001) and often simultaneously motivate animals to eat, drink, engage in sex, etc.…”
Section: Dopamine-beyond Learning Too?mentioning
confidence: 99%
“…7,8 Thousands of DBS implants are now performed each year for a growing number of movement disorders. [9][10][11] Nonetheless, despite the clinical successes of DBS, we still lack a fully formulated theory for how DBS works. [12][13][14] Since the inception of DBS as a clinical therapy, its mechanisms have been the focus of intense scientific study and debate.…”
Section: Introductionmentioning
confidence: 99%